2019
DOI: 10.1016/j.apcata.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Active site isolation in bismuth-poisoned Pd/SiO2 catalysts for selective hydrogenation of furfural

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…The catalytic hydrogenation of furfural is considered as one of the pivotal reactions to convert lignocellulose-based biomass into renewable chemicals and fuels. Therefore, after proving the successfully preparation of Ru–MoO x /CN catalyst with well-dispersed metal particles by one-pot pyrolysis method, direct hydrogenation of FAL to THFA was chosen as a model reaction to evaluate the catalytic performance. As shown in Table , the blank run (using CN-250A-350H only) gave essentially no activity in this system after 1 h of reaction, indicating that the Ru and/or MoO x particles in the catalysts might be the active sites for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic hydrogenation of furfural is considered as one of the pivotal reactions to convert lignocellulose-based biomass into renewable chemicals and fuels. Therefore, after proving the successfully preparation of Ru–MoO x /CN catalyst with well-dispersed metal particles by one-pot pyrolysis method, direct hydrogenation of FAL to THFA was chosen as a model reaction to evaluate the catalytic performance. As shown in Table , the blank run (using CN-250A-350H only) gave essentially no activity in this system after 1 h of reaction, indicating that the Ru and/or MoO x particles in the catalysts might be the active sites for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of the bimetallic catalyst determines that the main products are tetrahydrofurfuryl alcohol or the tautomeric mixtures of 5hydroxy-2-pentanone and 2-methyloxolan-2-ol. Cherkasov et al [62] synthesized a Bi-poisoned Pd catalyst (Bi isolates the Pd site by blocking the edge site primarily, altering the selectivity of the product). The results showed that at higher reaction temperature, Bi-poisoned Pd catalyst inhibited the oligomerization reaction of furfural and increased the generation of cyclopentanol.…”
Section: Amorphous Silica Supported Metals Catalystsmentioning
confidence: 99%
“…A 5 wt % Pd/SiO 2 catalyst, poisoned by bismuth(III), was used to prepare CPN from FF in the aqueous medium. 72 Bismuth helped to isolate the active sites on the palladium surface and minimized the oligomerization of FF. As the reaction temperature was increased, the major product changed from THFAL (at 50 °C) to FAL (100–150 °C) to CPN (>150 °C).…”
Section: Catalytic Conversion Of Ff Into Cpnmentioning
confidence: 99%
“…A 5 wt % Pd/SiO 2 catalyst, poisoned by bismuth­(III), was used to prepare CPN from FF in the aqueous medium . Bismuth helped to isolate the active sites on the palladium surface and minimized the oligomerization of FF.…”
Section: Catalytic Conversion Of Ff Into Cpnmentioning
confidence: 99%